2015
DOI: 10.1007/s00384-015-2258-y
|View full text |Cite|
|
Sign up to set email alerts
|

Outpatient, non-antibiotic management in acute uncomplicated diverticulitis: a prospective study

Abstract: Previous results of low complication rates with the non-antibiotic policy were confirmed. The new policy of outpatient management without antibiotics in acute uncomplicated diverticulitis is now shown to be feasible, well functioning, and safe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 32 publications
3
64
0
1
Order By: Relevance
“…One recently published prospective study went further by a step and treated UD without antibiotics [21] , based on the results of a randomized CT comparing antibiotics with no antibiotics in its population cohort [9] . It is of interest to note that the results without antibiotics seemed comparable to the other studies testing various types of antibiotics in an out-patient setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One recently published prospective study went further by a step and treated UD without antibiotics [21] , based on the results of a randomized CT comparing antibiotics with no antibiotics in its population cohort [9] . It is of interest to note that the results without antibiotics seemed comparable to the other studies testing various types of antibiotics in an out-patient setting.…”
Section: Discussionmentioning
confidence: 99%
“…Only 5 studies reported the recurrence of diverticulitis as requiring further treatment with or without hospitalization during a period of longer follow-up [15,17,[19][20][21] . The period of follow-up in which recurrence was noted was highly variable ranging between 1 and 24 months.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…El fundamento de esta estrategia ha sido que cualquier inflamación resulta en microperforación del divertículo, teniendo como consecuencia contaminación del peritoneo. Sin embargo, estudios recientes plantean la necesidad de reevaluar esta indicación en casos no complicados 69,70 . Chabok y cols.…”
Section: Fármacosunclassified
“…A recent study has shown that outpatient, non-antibiotic management of acute uncomplicated diverticulitis may be a feasible and safe option. (22) However the ability to identify these patients is still difficult. Bilirubin, WBC and CRP are commonly measured as part of a standard workup for abdominal pain in the emergency department.…”
Section: Introductionmentioning
confidence: 99%